1991
DOI: 10.1007/bf02193752
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of glucocorticoids on lymphocyte proliferation in depression

Abstract: European "D~I rg'~'~ Ir t"l~'I r Archives of 1~ y Ik.lllOl.lkl. Summary. Twelve severely depressed patients and 13 healthy controls were studied under baseline, metyrapone and metyrapone plus dexamethasone pretreated conditions. Lymphocyte proliferation data were obtained by concanavalin A, phytohaemagglutinin and pokeweed mitogen (PWM) stimulation. There was a decrease in PWM-induced B-cell proliferation and an increase in inhibition of spontaneous leucocyte proliferation by dexamethasone added in vitro follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Although a small number of studies have investigated the functional sensitivity of PBMCs from depressed patients to the inhibitory effects of cortisol, all of them showed an increased GCs resistance as determined by in vitro or in vivo challenge with DEX (Lowy et al, 1988;Rupprecht et al, 1991b;Miller et al, 1999). In agreement with these reports, in the present study a group of untreated patients showed an expected correlation between a reduced GR number and an attenuated effect of cortisol on PHA-induced lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…Although a small number of studies have investigated the functional sensitivity of PBMCs from depressed patients to the inhibitory effects of cortisol, all of them showed an increased GCs resistance as determined by in vitro or in vivo challenge with DEX (Lowy et al, 1988;Rupprecht et al, 1991b;Miller et al, 1999). In agreement with these reports, in the present study a group of untreated patients showed an expected correlation between a reduced GR number and an attenuated effect of cortisol on PHA-induced lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…Mononuclear cells (6 x 10 6 cells) were divided into 4 groups (1.5 x 10 6 cells in each one) and stimulated with phytohemagglutinin (PHA, 5ug/ml) in RPMI 1640 supplemented with 10% fetal calf serum, 1M Hepes, 2mM/L glutamine (all from GIBCO) and 10mg/ ml gentamicine (SIGMA) in the presence of dexamethasone (10 -6 M, SIGMA), IL-2 (100 Cetus Unit), epinephrine 10 -7 M and serotonin 10 -4 M for up to 10 days in a humidified chamber with 95% air and 5% carbon dioxide. The doses of dexamethasone, epinephrine and serotonin were based on the literature 17 and previous experiment done in our laboratory and represent the increase of cortisol generated during stress and the adrenergic stress respectively 17,18 . Cells were subsequently harvested at 3 day intervals, washed and stained with the same FITC and PE conjugated monoclonal antibodies that react with the selected cell surface antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, impaired lymphocyte sensitivity to glucocorticoids has also been observed in patients with major depression. [14, 15]. …”
Section: Introductionmentioning
confidence: 99%